3RS initiative in Malaysian public university: A case study of green team, International Islamic University Malaysia - Hashim, Khairusy Syakirin Has-Yun; Mohammed, Abdul Hakim; Mohamed Shah Redza, Haneesa Zahidah; Manta-Khaira, Kim (2011)

(untitled)
Waste issues have been discussed in every nation. Reports and discussion papers retrieved in developed, developing and third world countries, shows that wastes are common issues and problems. One of the solutions is implementing the Waste Management Hierarchy. The aim of a Waste Management Hierarchy is to minimize the amount of waste from entering the landfill/dump sites. Three top initiatives in the waste management hierarchy is the 3Rs initiative, i.e. Reduce, Reuse and Recycle. As waste management is a subset of environmental management, it can also be a subset of Facilities Management. To cultivate a 3R culture in a society, it is important to train groups of people by creating an awareness programme towards implementing 3Rs initiative. It is essential to start by educating people with knowledge, especially among students in universities. Thus, the aim of this paper is to explore the current stage of 3Rs awareness among university students by using questionnaires and case study approach in the International Islamic University Malaysia. It is also the aim of this paper to suggest methods in creating awareness among students in universities by developing a Waste Minimization Awareness Model (WMAM).